Magnetically tunable liquid dielectric with giant dielectric permittivity based on core-shell superparamagnetic iron oxide - Vinayasree, S.; Nitha, T. S.; Tiwary, C. S.; Ajayan, P. M.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2018)
A liquid dielectric based on a core-shell architecture having a superparamagnetic iron oxide core and a shell of silicon dioxide was synthesized. The frequency dependence of dielectric properties was evaluated for different concentrations of iron oxide. The dependence of magnetic field on the dielectric properties was also studied. Aqueous ferrofluid exhibited a giant dielectric constant of 6.4 x 10(5) at 0.1 MHz at a concentration of 0.2 vol% and the loss tangent was 3. The large rise in dielectric constant at room temperature is modelled and explained using percolation theory and Maxwell-Wagner-Sillars type polarization. The ferrofluid is presumed to consist of nanocapacitor networks which are wired in series along the lateral direction and parallel along longitudinal direction. On the application of an external magnetic field, the chain formation and its alignment results in the variation of dielectric permittivity.